EKSPEKTASI PASAR ATAS KEBIJAKAN RESUFFLE KABINET KERJA: UJI KEKUATAN (ROBUSTNESS) METODA EVENT STUDY - Bayu Sindhu Raharja (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This research aims to test the market expectation on minister reshuffle announcement in Indonesia and answer the doubt of event study existences. Using 61 days as a windows period and all of construction firms as research sample, it confirm the positive respond of investor on minister reshuffle announcement and no doubt on robustness of event study method. This research also capture the anomaly of market condition, as like the better performance of risk-free rate return than market return. It being sweet counterblow to efficient market hypothesis.Keywords: exchange rate, political, market condision